2016
DOI: 10.1109/tpwrd.2015.2437717
|View full text |Cite
|
Sign up to set email alerts
|

A Reliability Evaluation of Offshore HVDC Grid Configuration Options

Abstract: This paper details a methodology for investigating the reliability of different offshore grid design options for the connection of offshore wind power to shore. The methodology uses a sequential Monte Carlo based technique that allows investigation of realistic offshore phenomena such as the weather dependency of component repair times. A number of case studies are examined for the connection to shore of a cluster of far offshore wind farms and a cost benefit analysis is performed which compares the capital co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 10 publications
(15 reference statements)
0
31
0
Order By: Relevance
“…In order to populate the database shown in Table 2 a number of papers and reports which focussed on reliability analysis and offshore cables were reviewed [3][4][5][6][7][8][9][10]. The reliability figures used were then converted from a number of different formats to be represented as failures / year in order to allow for comparison between different cable lengths and ratings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to populate the database shown in Table 2 a number of papers and reports which focussed on reliability analysis and offshore cables were reviewed [3][4][5][6][7][8][9][10]. The reliability figures used were then converted from a number of different formats to be represented as failures / year in order to allow for comparison between different cable lengths and ratings.…”
Section: Discussionmentioning
confidence: 99%
“…As a result of this a number of authors have had to estimate failure rates such as the figures found in [3] which creates an estimate based on other literature, [4][5][6] which estimate failure rates through observation of onshore transmission reliability data and [7] which estimates a failure rate through discussion with cable manufacturers.…”
Section: Introductionmentioning
confidence: 99%
“…As such, the series equivalent reliability model of the VSC station can be represented by a typical two-state Markov model using (6.a) and (6.b). The outage data of the VSC-HVDC system are listed in the Appendix [16]- [17], [24]. The equivalent reliability model of the VSC station is listed in Table III 2) DC transmission line: The system includes two main common parallel DC transmission lines using submarine cables.…”
Section: Combined Wfs and Vsc-hvdc Reliability Modelmentioning
confidence: 99%
“…However, the failure rates and repair time of the offshore VSC-HVDC system are quite different from the onshore cases [17]. For example, the repair work significantly depends on the weather conditions such as wind regime and wave height.…”
Section: Effect Of the Repair Time Of Offshore Vsc-hvdc Systemmentioning
confidence: 99%
“…Meshed network configuration is more reliable than radial due to redundant supply channels but incur higher cable cost. Any topology can be configured, once technical and economic benefits of the network operators have been dealt with [3].…”
Section: Introductionmentioning
confidence: 99%